On the problem of plotting regional analytical approximations of elements of the elements of anomalous gravity field - A. I. Yakimchik (Геофизический журнал, 2009)
The problems have been considered, without the decision of which per se, plotting of linear analytical approximations of the gravity field given on the Earth surface is impossible. It is stated that secrecy of gravimetric data of territory of Ukraine is the basic obstacle for the calculation of regional analytical approximations of the anomalous fields elements. The decision of problems of information preservation and its effective use could be carried out through modern information technologies and creation of data banks.